Theoretical framework for an analysis of the recent criminal law reforms in Poland - Utrat-Milecki Jarosław (Crimen (Beograd), 2025)
The analysis of criminal law reforms in Poland from the perspective of criminal punishment as a complex legal and social institution of a processual nature is intended to present the concept of a critical examination of the punitiveness of the penal system. That critical approach is intended to help researchers and specialists in the field of criminal policy to deal with penal reforms and penal practices; thus, the analysis is not only for researchers but also for practising lawyers.